Novel technique for measuring the 3D geometric size of fruit cells - Qiang, Hongli; Li, Baolong; Li, Zhiguo; Tchuenbou-Magaia, Fideline; Wei, Boyuan; Liu, Yande (International Journal of Agricultural and Biological Engineering, 2025)
The size and shape of individual fruit cells are key indicators of a fruit’s physiological condition and overall quality. However, due to the three-dimensional (3D) nature of fruit cells, existing biomicroscopes are not capable of efficiently or accurately characterizing their 3D geometry. In this work, a novel microscope system integrated with computer software was developed to enable precise 3D geometrical characterization of fruit cells. To validate the system’s effectiveness, tomatoes and strawberries at two different stages of ripeness were used as test samples. First, the front and bottom views of the fruit cells were captured. Subsequently, the developed software was used to measure the 3D geometric size of each individual cell. Key performance parameters of the developed 3D microscope, including overall magnification, aperture diameter, resolution, and field of view area, were carefully measured and evaluated. The experiment revealed differences in the length D1, thickness D2, width D3, and geometric mean diameter (GMD) of single cells of tomatoes and strawberries; these differences were 18.18%, 4.6%, 9.8%, and 29.7%, 10.7%, 12.6%, respectively. Furthermore, 3D geometrical data, including surface area S, volume V, and sphericity φ of single cells, were successfully obtained. This demonstrated that the developed microscope system can efficiently and accurately capture and characterize the true 3D geometry of cells, emphasizing its scientific value. Keywords: cell observation instrument, 3D geometric information, fruit single cell, dual-viewpoint, orthogonal observationDOI: 10.25165/j.ijabe.20251803.9581Citation: Qiang H L, Li B L, Li Z G, Tchuenbou-Magaia F, Wei B Y, Liu Y D. Novel technique for measuring the 3D geometric size of fruit cells. Int J Agric & Biol Eng, 2025; 18(3): 257–264.